2011
DOI: 10.1088/0031-9155/56/8/004
|View full text |Cite
|
Sign up to set email alerts
|

Physical and clinical performance of the mCT time-of-flight PET/CT scanner

Abstract: Time-of-flight (TOF) measurement capability promises to improve PET image quality. We characterized the physical and clinical PET performance of the first Biograph mCT TOF PET/CT scanner (Siemens Medical Solutions USA, Inc.) in comparison with its predecessor, the Biograph TruePoint TrueV. In particular, we defined the improvements with TOF. The physical performance was evaluated according to the National Electrical Manufacturers Association (NEMA) NU 2-2007 standard with additional measurements to specificall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
409
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 454 publications
(435 citation statements)
references
References 10 publications
15
409
1
2
Order By: Relevance
“…The delineated lesion is also shown in green in the figure. Consistent with the previous findings (22)(23)(24)(25)(26), OSEM 1 TOF 1 PSF produced visually the best image among the chosen 4 reconstruction algorithms with their default settings. In addition, quantitative assessment supported the fact that OSEM 1 TOF 1 PSF produced the best image with an SNR of 9.1 in the liver, whereas the SNR of OSEM, OSEM 1 PSF, and OSEM 1 TOF were 5.2, 5.5, and 8.5, respectively.…”
Section: Change Of Image Features Over Default Reconstruction Settingssupporting
confidence: 87%
See 2 more Smart Citations
“…The delineated lesion is also shown in green in the figure. Consistent with the previous findings (22)(23)(24)(25)(26), OSEM 1 TOF 1 PSF produced visually the best image among the chosen 4 reconstruction algorithms with their default settings. In addition, quantitative assessment supported the fact that OSEM 1 TOF 1 PSF produced the best image with an SNR of 9.1 in the liver, whereas the SNR of OSEM, OSEM 1 PSF, and OSEM 1 TOF were 5.2, 5.5, and 8.5, respectively.…”
Section: Change Of Image Features Over Default Reconstruction Settingssupporting
confidence: 87%
“…Thus, the impact of the partial-volume effect can be neglected. Previous studies (22)(23)(24)(25)(26) demonstrated that OSEM 1 PSF 1 TOF produced better image quality than other methods in terms of SNR, contrast, and lesion detectability. Therefore, in this study, the tumor VOIs were delineated on the image reconstructed by OSEM 1 PSF 1 TOF with default settings and then applied to the other methods.…”
Section: Tumor Segmentationmentioning
confidence: 97%
See 1 more Smart Citation
“…However, we observed that TOF did not improve quantification of SUV, as shown by Jacoby et al [4], who also observed that the use of TOF produced substantially higher image contrast and signal-to-noise ratios.…”
Section: Discussionsupporting
confidence: 71%
“…We imaged four consenting patients under approved IRB (institutional review board) protocol, which followed patient imaging with whole‐body mCT PET/CT from Siemens (Jakoby et al., 2011). The patients (all male) were cancer patients requiring clinical whole‐body PET/CT.…”
Section: Methodsmentioning
confidence: 99%